Slit copper material, components for electronic and electrical equipment, bus bar, heat dissipation substrate
Patent Information
- Application Number
- KR1020237005294
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-19
- Filing Date
- 2021-10-20
- Publication Date
- 2026-09-09
- Estimated Expiration
- 2041-10-20
Smart Images

Figure 112023017266809-PCT00005_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a slit copper material suitable for components for electronic and electrical devices, such as bus bars and heat dissipation substrates, and components for electronic and electrical devices, bus bars, and heat dissipation substrates made using the slit copper material.
[0002] The present application claims priority based on Japanese Patent Application No. 2020-178070 filed in Japan on October 23, 2020, and Japanese Patent Application No. 2021-170961 filed in Japan on October 19, 2021, and incorporates the contents thereof herein by reference. Background Technology
[0003] Conventionally, highly conductive copper or copper alloys are used in components for electronic and electrical devices, such as bus bars and heat dissipation substrates.
[0004] Here, in order to reduce current density and dissipate heat caused by Joule heating in conjunction with the increase in current of electronic and electrical devices, pure copper materials such as oxygen-free copper with excellent conductivity are applied to electronic and electrical device components used in these devices.
[0005] However, in conventional pure copper materials, the bending processability required when forming electronic devices or electrical devices is insufficient, and there were problems such as cracking occurring, especially when performing strict processing such as edge-wise bending.
[0006] Thus, Patent Document 1 discloses an insulated flat copper wire having a flat copper wire formed of oxygen-free copper with a 0.2% yield strength of 150 MPa or less.
[0007] In the copper rolled plate described in Patent Document 1, since the 0.2% yield strength is suppressed to 150 MPa or less, it was possible to suppress the decrease in yield strength characteristics in the bent portion when edgewise bending is performed.
[0008] However, recently, regarding copper materials constituting the electronic and electrical equipment components described above, there is a requirement to further improve the conductivity in order to sufficiently suppress heat generation when a large current flows and to enable use in applications where pure copper materials were previously used.
[0009] In addition, regarding the electronic and electrical equipment components described above, there are cases where complex bending processes are performed, so it was necessary to further improve bendability compared to conventional methods.
[0010] In addition, regarding the electronic and electrical equipment components described above, miniaturization and weight reduction are required, and thus sufficient strength is required. Prior art literature
[0011] Japanese Published Patent Application No. 2013-004444 The problem to be solved
[0012] The present invention is made in consideration of the aforementioned circumstances and aims to provide a slit copper material having high conductivity, strength, and excellent bendability, and components for electronic and electrical devices, bus bars, and heat dissipation substrates made using the slit copper material. means of solving the problem
[0013] In order to solve this problem, the inventors carefully examined the matter and found that, in the case of slit copper material, it is necessary to appropriately control the crystal structure to improve bendability while maintaining strength. Specifically, they found that by appropriately controlling the crystal grain size in the central and surface layers of the plate thickness, it is possible to improve strength and bendability in a good balance to a higher level than conventional methods.
[0014] The present invention is based on the findings described above, and a slit copper material related to one embodiment of the present invention is a slit copper material having a purity of Cu of 99.96 mass% or more and a ratio W / t of plate width W to plate thickness t of 10 or more, and is characterized by having an electrical conductivity of 97.0% IACS or more, and a ratio B / A of the average crystal grain size A of the center of the plate thickness to the average crystal grain size B of the surface layer of the plate thickness being within the range of 0.80 or more and 1.20 or less, and the average crystal grain size A of the center of the plate thickness being 25 μm or less.
[0015] In addition, slit copper material refers to a copper plate that has been slit to a predetermined width.
[0016] Also, in this specification, the center of the plate thickness is defined as the area from 25% to 75% of the total thickness from the surface in the plate thickness direction.
[0017] In addition, in this specification, the plate thickness surface layer is defined as the area from the surface in the plate thickness direction up to 20% of the total thickness.
[0018] According to the slit copper material of this composition, since the purity of Cu is 99.96 mass% or higher, conductivity can be secured, and it is possible to make the conductivity 97.0% IACS or higher.
[0019] In addition, since the average crystal grain size A at the center of the plate thickness is 25 μm or less, it is possible to improve bendability and yield strength. Also, the occurrence of burrs during slitting can be suppressed, and thus the occurrence of cracks originating from burrs during bending can be suppressed.
[0020] In addition, since the ratio B / A of the average crystal grain size A at the center of the plate thickness and the average crystal grain size B at the surface of the plate thickness is within the range of 0.80 or more and 1.20 or less, localized concentration of stress during processing can be suppressed, thereby improving bendability.
[0021] Here, in the slit copper material related to one embodiment of the present invention, it is preferable to contain Mg in a range of greater than 10 massppm and less than 100 massppm, and to have a heat resistance temperature of 150°C or higher.
[0022] In this case, since Mg is contained within the range described above, Mg is dissolved in the copper matrix, making it possible to improve strength and heat resistance without significantly reducing conductivity. In addition, since the heat resistance temperature is 150°C or higher, it can be used stably even in high-temperature environments.
[0023] In addition, in the slit copper material related to one embodiment of the present invention, it is preferable that the 0.2% yield strength in a direction parallel to the rolling direction is greater than 150 MPa.
[0024] In this case, the 0.2% yield strength in the direction parallel to the rolling direction is sufficiently high, and the occurrence of burrs during slitting can be further suppressed, thereby suppressing the occurrence of cracks originating from burrs during bending processing.
[0025] In addition, in a slit copper material related to one embodiment of the present invention, it is preferable to exclude measurement points where the CI value is 0.1 or less and analyze the results, and for the ratio of the number of grains in which the aspect ratio b / a, represented by the major axis a and minor axis b of the grain (including twins) at the center of the plate thickness, is 0.3 or less, to be 90% or less of the total number of measured grains.
[0026] In this case, since the ratio of grains with an aspect ratio b / a of 0.3 or less is 90% or less of the total measured grains, the degree of processing is suppressed, and bending workability can be further improved while maintaining yield strength.
[0027] In addition, regarding a slit copper material related to one embodiment of the present invention, the slit copper material is measured by the EBSD method in steps of measurement intervals that are 1 / 10 or less of the average crystal grain size A at the center of the plate thickness, and the total area in multiple fields is 10,000 μm such that a total of 1,000 or more crystal grains are included at the center of the plate thickness. 2 In the measurement area exceeding the above, the measurement results are analyzed using the data analysis software OIM to obtain the CI value for each measurement point, measurement points with a CI value of 0.1 or less are excluded to analyze the orientation difference of each grain, and the length of the small angle grain boundary and subgrain boundary, which is the boundary between measurement points where the orientation difference between adjacent measurement points is 2° or more and less than 15°, is L. LB , the length of the major angle grain boundary, which is the boundary between measurement points where the orientation difference between adjacent measurement points is 15° or more, is L HB When done as, L LB / (L LB + L HB It is desirable to have a relationship of ) > 10%.
[0028] In this case, since the length of the small angle grain boundary and subgrain boundary is sufficiently secured, a region with high dislocation density is secured, making it possible to improve strength (yield strength) through work hardening.
[0029] In addition, in a slit copper material related to one embodiment of the present invention, when the crystal orientation distribution function obtained from texture analysis by the EBSD method is expressed in Euler angles at the center of the plate thickness, it is preferable that the average value of the orientation density in the range of φ2 = 20°, φ1 = 20° to 50°, and Φ = 40° to 70° is 1.0 or higher and less than 20.0.
[0030] In this case, it becomes possible to obtain good bendability while maintaining higher yield strength.
[0031] In addition, in the slit copper material related to one embodiment of the present invention, the thickness may be within the range of 0.1 mm or more and 10 mm or less.
[0032] In this case, since the thickness is within the range of 0.1 mm or more and 10 mm or less, by performing stamping or bending processes on this slit copper material, components for electronic and electrical equipment such as bus bars and heat dissipation substrates can be formed.
[0033] In addition, in the slit copper material related to one aspect of the present invention, it is preferable to have a metal plating layer on the surface.
[0034] In this case, the slit copper material may be said to have a slit copper material body and a metal plating layer formed on the surface of the slit copper material body. The slit copper material body has the same characteristics as the slit copper material related to one embodiment of the present invention described above. Because it has a metal plating layer on its surface, it is particularly suitable as a material for components of electronic and electrical devices, such as bus bars and heat dissipation substrates.
[0035] In addition, the metal plating layer may include, for example, Sn plating, Ag plating, Ni plating, etc. Furthermore, in one embodiment of the present invention, "Sn plating" includes pure Sn plating or Sn alloy plating, "Ag plating" includes pure Ag plating or Ag alloy plating, and "Ni plating" includes pure Ni plating or Ni alloy plating.
[0036] An electronic or electrical device component related to one embodiment of the present invention is characterized by being made using the slit copper material described above. Furthermore, an electronic or electrical device component in one embodiment of the present invention includes a bus bar, a heat dissipation substrate, etc.
[0037] As the electronic and electrical equipment component of this configuration is manufactured using slit copper material having high yield strength and excellent bendability as described above, it is possible to achieve miniaturization and weight reduction.
[0038] A bus bar related to one embodiment of the present invention is characterized by being made of the slit copper material described above.
[0039] As the bus bar of this configuration is manufactured using a slit copper material having high yield strength and excellent bendability as described above, it is possible to achieve miniaturization and weight reduction.
[0040] A heat dissipation substrate related to one embodiment of the present invention is characterized by being made using the slit copper material described above.
[0041] As the heat dissipation substrate of this configuration is manufactured using a slit copper material having high yield strength and excellent bendability as described above, it is possible to achieve miniaturization and weight reduction. Effects of the invention
[0042] According to one aspect of the present invention, it is possible to provide a slit copper material having high conductivity, strength, and excellent bendability, and components for electronic and electrical devices, bus bars, and heat dissipation substrates made using the slit copper material. Brief explanation of the drawing
[0043] FIG. 1 is a flowchart of a method for manufacturing a slit copper material according to the present embodiment. Specific details for implementing the invention
[0044] Below, a slit copper material, which is an embodiment of the present invention, will be described.
[0045] In the slit copper material of the present embodiment, a copper plate is obtained by slitting a copper plate to a predetermined width. In the slit copper material of the present embodiment, the ratio W / t of the plate width W to the plate thickness t is 10 or more.
[0046] The slit copper material of the present embodiment has a purity of Cu of 99.96 mass% or more.
[0047] In addition, the slit copper material of the present embodiment may contain Mg in a range of more than 10 massppm and less than 100 massppm.
[0048] Accordingly, the slit copper material contains Cu: 99.96 mass% or more and any Mg: more than 10 massppm and less than 100 massppm, and the remainder may be considered an unavoidable impurity. In addition, Mg may not be intentionally added and may be contained as an unavoidable impurity, in which case the Mg content may be 10 massppm or less.
[0049] In addition, in the slit copper material of this embodiment, the conductivity is 97.0% IACS or higher.
[0050] In addition, in the slit copper material of the present embodiment, the ratio B / A of the average crystal grain size A at the center of the plate thickness and the average crystal grain size B at the surface layer of the plate thickness is within the range of 0.80 or more and 1.20 or less. Also, the average crystal grain size A at the center of the plate thickness is 25 μm or less.
[0051] In addition, in this embodiment, the center of the plate thickness is defined as the region from the surface in the plate thickness direction to 25% to 75% of the total thickness. Also, the surface layer of the plate thickness is defined as the region from the surface in the plate thickness direction to 20% of the total thickness.
[0052] In addition, in the slit copper material of the present embodiment, it is preferable to exclude measurement points where the CI value is 0.1 or less and analyze the results, and for the ratio of the number of grains in which the aspect ratio b / a, represented by the major axis a and minor axis b of the grain (including twins) at the center of the plate thickness, is 0.3 or less, to be 90% or less of the total number of measured grains.
[0053] In addition, in the slit copper material of the present embodiment, the slit copper material is measured by the EBSD method in steps of measurement intervals that are 1 / 10 or less of the average crystal grain size A at the center of the plate thickness. The total area in multiple fields is 10,000 μm so that a total of 1,000 or more crystal grains are included at the center of the plate thickness. 2 For the measurement area exceeding the above, the measurement results are analyzed using the data analysis software OIM to obtain the CI value for each measurement point. Measurement points with a CI value of 0.1 or less are excluded. The orientation difference of each grain is analyzed using the data analysis software OIM. The length of the small angle grain boundary and subgrain boundary, which is the boundary between measurement points where the orientation difference between adjacent measurement points is 2° or more and less than 15°, is L. LB Let L be the length of the large angle grain boundary, which is the boundary between measurement points where the bearing difference between adjacent measurement points is 15° or more. HB ...to be done. At this time, L LB / (L LB + L HB It is desirable to have a relationship of ) > 10%.
[0054] In addition, in the slit copper material of the present embodiment, when the crystal orientation distribution function obtained from texture analysis by the EBSD method is expressed in Euler angles at the center of the plate thickness, it is preferable that the average value of the orientation density in the range of φ2 = 20°, φ1 = 20° to 50°, and Φ = 40° to 70° is 1.0 or higher and less than 20.0.
[0055] In addition, in the slit copper material of the present embodiment, it is preferable that the 0.2% yield strength in the direction parallel to the rolling direction is greater than 150 MPa.
[0056] In addition, in the slit copper material of the present embodiment, when containing Mg, it is preferable that the heat resistance temperature be 150°C or higher.
[0057] Hereinafter, regarding the slit copper material of the present embodiment, the reasons for specifying the component composition, structure, and various characteristics as described above are explained below.
[0058] (Cu)
[0059] The higher the Cu content and the lower the relative impurity concentration, the higher the conductivity. For this reason, in this embodiment, the Cu content is set to 99.96 mass% or more.
[0060] In addition, in order to further improve the electrical conductivity of the slit copper material of the present embodiment, it is preferable to have a Cu content of 99.97 mass% or more, more preferable to have 99.98 mass% or more, and more preferable to have 99.99 mass% or more. Although there is no particular upper limit for the Cu content, it is kept below 99.9995 mass% because manufacturing costs increase.
[0061] (Mg)
[0062] Mg is an element that has the effect of improving strength without significantly reducing conductivity, as it is dissolved in the matrix phase of copper. In addition, by dissolving Mg in the matrix phase, the heat resistance temperature is improved. For this reason, Mg may be added to improve strength, heat resistance, etc.
[0063] Here, it is possible to exert the aforementioned effects by exceeding the Mg content of 10 massppm. On the other hand, by keeping the Mg content of less than 100 massppm, the decrease in conductivity can be suppressed.
[0064] For this reason, in the present embodiment, when adding Mg, it is preferable to have the Mg content greater than 10 massppm and less than 100 massppm.
[0065] In addition, to further improve strength, heat resistance, etc., it is more desirable to set the lower limit of the Mg content to 20 massppm or more, more desirable to set it to 30 massppm or more, and even more desirable to set it to 40 massppm or more. Meanwhile, to further suppress the decrease in electrical conductivity, it is more desirable to set the upper limit of the Mg content to less than 90 massppm, more desirable to set it to less than 80 massppm, and even more desirable to set it to less than 70 massppm.
[0066] In addition, if Mg is contained as an impurity without being intentionally added, the Mg content may be 10 mass ppm or less.
[0067] (Other unavoidable impurities)
[0068] Other unavoidable impurities other than the elements described above include Al, Ag, As, B, Ba, Be, Bi, Ca, Cd, Cr, Sc, rare earth elements, V, Nb, Ta, Mo, Ni, W, Mn, Re, Ru, Sr, Ti, Os, P, Co, Rh, Ir, Pb, Pd, Pt, Au, Zn, Zr, Hf, Hg, Ga, In, Ge, Y, Tl, N, S, Sb, Se, Si, Sn, Te, Li, etc. These unavoidable impurities may be contained within a range that does not affect the properties.
[0069] Here, it is desirable to keep the content of these unavoidable impurities low, as they may reduce conductivity.
[0070] (Average crystal grain size at the center of the plate thickness A)
[0071] In the slit copper material of the present embodiment, if the average crystal grain size A in the center of the plate thickness (the region from the surface in the plate thickness direction to 25% to 75% of the total thickness) is fine, excellent bendability and high yield strength are obtained. In addition, since the occurrence of burrs can be suppressed during slit processing, it is also possible to suppress cracks that occur starting from burrs during bending processing.
[0072] For this reason, in this embodiment, the average crystal grain size A at the center of the plate thickness is specified as 25 μm or less.
[0073] Here, in order to obtain even better bending processability and high yield strength in the slit copper material of the present embodiment, it is preferable to make the average crystal grain size A at the center of the plate thickness 20 μm or less, and more preferable to make it 15 μm or less. In addition, there is no particular limit on the lower limit of the average crystal grain size A at the center of the plate thickness, but substantially it is 1 μm or more.
[0074] (Ratio of average crystal grain size A at the center of the plate thickness to average crystal grain size B at the surface of the plate thickness B / A)
[0075] In the slit copper material of the present embodiment, if the crystal grain size is non-uniform, stress concentration occurs at the grain boundaries of coarse grains during processing, causing local deformation and accelerating the occurrence of cracks. Therefore, it is necessary to control the crystal grain size so that it is uniform in the plate thickness direction.
[0076] For this reason, in this embodiment, the ratio B / A of the average crystal grain size A of the center of the plate thickness (the region from the surface in the plate thickness direction to 25% to 75% of the total thickness) and the average crystal grain size B of the surface layer of the plate thickness (the region from the surface in the plate thickness direction to 20% of the total thickness) is set to a range of 0.80 or more and 1.20 or less.
[0077] Here, in the slit copper material of the present embodiment, the lower limit of the ratio B / A of the average crystal grain size A of the center of the plate thickness and the average crystal grain size B of the surface layer of the plate thickness is preferably 0.82 or higher, and more preferably 0.85 or higher. Meanwhile, the upper limit of the ratio B / A of the average crystal grain size A of the center of the plate thickness and the average crystal grain size B of the surface layer of the plate thickness is preferably 1.18 or lower, and more preferably 1.15 or lower.
[0078] (Aspect ratio b / a, expressed as the major axis a and minor axis b of the grain at the center of the plate thickness)
[0079] The aspect ratio, expressed as b / a where the major axis of a grain is denoted by a and the minor axis by b, is an indicator of the degree of workability of the material. As the proportion of grains with a small aspect ratio (i.e., grains with a large difference between the major axis a and the minor axis b) increases, the degree of workability also increases. By controlling the proportion of grains with an aspect ratio b / a of 0.3 or less at the center of the plate thickness to 90% or less of the total measured grains, bendability can be improved while maintaining yield strength. On the other hand, if the proportion of grains with an aspect ratio b / a of 0.3 or less exceeds 90% of the total grains, the proportion of grains with high work deformation increases, thereby impairing bendability.
[0080] From the above, in the present embodiment, the ratio of the number of grains in which the aspect ratio b / a of the grain is 0.3 or less is set to be 90% or less of the total number of measured grains. Furthermore, within the above-mentioned range, the ratio of the number of grains in which the aspect ratio b / a is 0.3 or less is particularly preferably 80% or less, and more preferably 50% or less. Although there is no particular limit on the lower limit of the ratio of the number of grains in which the aspect ratio b / a is 0.3 or less, it is preferably 1% or more.
[0081] Here, the CI value (reliability index) when analyzed by the analysis software OIM of the EBSD device becomes smaller when the determination pattern of the measurement point is unclear, and when the CI value is 0.1 or less, it is difficult to trust the analysis result. Therefore, in this embodiment, low-reliability measurement points with a CI value of 0.1 or less are excluded when evaluating the aspect ratio.
[0082] (Ratio of grain boundary and subgrain boundary length: L LB / (L LB + L HB ))
[0083] Regarding grain boundaries, since small-diameter grain boundaries and sub-grain boundaries are regions with a high density of dislocations introduced during processing, the ratio of the length of small-diameter grain boundaries and sub-grain boundaries to the total grain boundaries L LB / (L LB + L HB In terms of controlling the structure so that ) exceeds 10%, it becomes possible to improve strength (yield strength) through work hardening accompanied by an increase in dislocation density.
[0084] In addition, the ratio of the small angle grain boundary and subgrain boundary length L LB / (L LB + L HB ) is preferably 15% or more within the above-mentioned range, and furthermore, 20% or more is preferable.
[0085] Here, in order to have sufficient bending workability while maintaining strength (yield strength), the ratio of the small diameter angle grain boundary and the subgrain boundary length L LB / (L LB + L HB ) is preferably 80% or less, and more preferably 70% or less.
[0086] (Average value of orientation density in the range of φ2 = 20°, φ1 = 20°–50°, Φ = 40°–70°)
[0087] Euler angles represent crystal orientation based on the relationship between the sample coordinate system and the crystal axes of individual crystal grains. Crystal orientation is expressed by rotating (φ1, Φ, φ2) around the (ZXZ) axis, respectively, from a state where the crystal axes (XYZ) coincide. By plotting the ODF (crystal orientation distribution function) in three-dimensional Euler space using a series expansion method, it becomes possible to verify the distribution of crystal orientation density within the measurement range. This orientation density distribution sets the completely random orientation state obtained from standard powder samples, etc., as 1. For example, if the orientation density of a certain orientation is 3, it means that that orientation exists three times as often as the random orientation.
[0088] At the center of the plate thickness, the orientation density in the range of φ2 = 20°, φ1 = 20° to 50°, and Φ = 40° to 70°, when expressed as Euler angles (φ1, Φ, φ2), is mainly formed by rolling.
[0089] Since the average value of the orientation density described above is 1.0 or higher, sufficiently high yield strength can be obtained. On the other hand, since the average value of the orientation density described above is less than 20.0, it becomes possible to obtain good bending workability while maintaining yield strength.
[0090] Here, the lower limit of the average value of the orientation density described above is more preferably 1.2 or higher, and even more preferably 1.5 or higher. Meanwhile, the upper limit of the average value of the orientation density described above is more preferably 18 or lower, and even more preferably 15 or lower.
[0091] (Challenge rate: 97.0% IACS or higher)
[0092] In the copper alloy of the present embodiment, the conductivity is 97.0% IACS or higher.
[0093] By making the conductivity 97.0% IACS or higher, heat generation during current flow is suppressed, making it possible to use it well as a component for electronic and electrical equipment such as terminals, bus bars, and heat dissipation substrates as a replacement for conventional pure copper materials.
[0094] In addition, it is preferable that the conductivity be 97.5% IACS or higher, more preferable that it be 98.0% IACS or higher, more preferable that it be 98.5% IACS or higher, and even more preferable that it be 99.0% IACS or higher. The upper limit of the conductivity is not particularly limited, but it is preferable that it be 103.0% IACS or lower.
[0095] (0.2% yield strength in the direction parallel to the rolling direction: greater than 150 MPa)
[0096] In the slit copper material of the present embodiment, if the 0.2% yield strength in the direction parallel to the rolling direction is greater than 150 MPa, the occurrence of burrs during slitting can be suppressed, and the occurrence of cracks originating from burrs during bending processing can be suppressed.
[0097] Here, the 0.2% yield strength in the direction parallel to the rolling direction is more preferably 175 MPa or higher, and even more preferably 200 MPa or higher.
[0098] In addition, although no upper limit is set for the 0.2% yield strength, it is desirable to keep the 0.2% yield strength 500 MPa or less in order to avoid a decrease in productivity due to the coiling habit of the coil when using coil-wound raw material.
[0099] (Heat resistance temperature: 150 ℃ or higher)
[0100] In the slit copper material of the present embodiment, when the heat resistance temperature is high, softening due to recrystallization is unlikely to occur even at high temperatures, making it possible to apply it to conductive members used in high-temperature environments.
[0101] For this reason, in the present embodiment, it is preferable that the heat resistance temperature be 150°C or higher.
[0102] In addition, in this embodiment, the heat resistance temperature is measured in accordance with the Technical Standard JCBA T325:2013 of the Copper Industry Association, at which the Vickers hardness decreases to 80% of the initial value.
[0103] Here, the heat resistance temperature described above is more preferably 175 ℃ or higher, more preferably 200 ℃ or higher, even more preferably 225 ℃ or higher, and most preferably 250 ℃ or higher. The upper limit of the heat resistance temperature is not particularly limited, but is preferably 600 ℃ or lower.
[0104] Next, a method for manufacturing a slit copper material of the present embodiment having such a configuration will be explained with reference to the flowchart shown in FIG. 1.
[0105] (Melting and Casting Process S01)
[0106] First, a copper raw material is melted to obtain a molten copper bath. If necessary, Mg is added to adjust the composition. Additionally, when adding Mg, the elemental element or a master alloy may be used. Furthermore, a raw material containing the elements described above may be melted together with the copper raw material. Additionally, recycled materials and scrap materials may be used.
[0107] Here, it is preferable that the copper raw material be so-called 4N Cu with a purity of 99.99 mass% or higher, or so-called 5N Cu with a purity of 99.999 mass% or higher.
[0108] In order to reduce the hydrogen concentration during dissolution, it is desirable to perform the dissolution in an atmosphere of an inert gas atmosphere (e.g., Ar gas) with a low vapor pressure of H2O, and to minimize the holding time during dissolution.
[0109] Then, the compositionally adjusted molten copper is poured into a mold to produce an ingot. In addition, when considering mass production, it is desirable to use a continuous casting method or a semi-continuous casting method.
[0110] (Homogenization / Solution Process S02)
[0111] Next, a heat treatment is performed to homogenize and solution-treat the obtained ingot. In the interior of the ingot, intermetallic compounds, etc., may exist, which are generated as impurities are concentrated as segregation during the solidification process. Therefore, in order to eliminate or reduce these segregations and intermetallic compounds, a heat treatment is performed by heating the ingot to a temperature of 300°C or higher and 1080°C or lower. This causes the impurities to diffuse homogeneously within the ingot. Furthermore, it is preferable to carry out this homogenization / solution-treating process S02 in a non-oxidizing or reducing atmosphere.
[0112] Here, if the heating temperature is below 300 ℃, solution treatment becomes incomplete, and there is a risk that a large amount of intermetallic compounds will remain in the matrix phase. On the other hand, if the heating temperature exceeds 1080 ℃, some of the copper material becomes liquid, and there is a risk that the structure or surface condition will become non-uniform. Therefore, the heating temperature is set in the range of 300 ℃ or higher and 1080 ℃ or lower.
[0113] In addition, to improve the efficiency of the rough rolling described later and to homogenize the microstructure, hot rolling may be performed after the aforementioned homogenization / solution process S02. It is preferable that the hot working temperature be within the range of 300°C or higher and 1080°C or lower.
[0114] (Rough rolling process S03)
[0115] Rough rolling is performed to process the material into a predetermined shape. Additionally, although there are no specific limitations on the temperature conditions in this rough rolling process S03, it is preferable to keep the temperature within the range of -200°C to 200°C, which is used for cold or hot rolling, in order to suppress recrystallization or to improve dimensional accuracy; room temperature is particularly preferred. Here, uniform deformation is introduced into the material, thereby obtaining uniform recrystallized grains in the intermediate heat treatment process S04 described later. Therefore, it is preferable that the total deformation rate be 50% or more, more preferable that it be 60% or more, and even more preferable that it be 70% or more. Furthermore, it is preferable that the deformation rate per pass be 20% or more, more preferable that it be 30% or more, and even more preferable that it be 40% or more.
[0116] (Intermediate heat treatment process S04)
[0117] After the rough rolling process S03, heat treatment is performed to obtain a recrystallized structure. In addition, the rough rolling process S03 and the intermediate heat treatment process S04 may be repeated.
[0118] Here, since this intermediate heat treatment process S04 is substantially the final recrystallization heat treatment, the crystal grain size of the recrystallized structure obtained in this process becomes nearly equivalent to the final crystal grain size. Therefore, in this intermediate heat treatment process S04, it is desirable to select appropriate heat treatment conditions so that the average crystal grain size at the center of the plate thickness is 25 μm or less.
[0119] In addition, in order to make the average value of the orientation density in the range of φ2 = 20°, φ1 = 20° to 50°, and Φ = 40° to 70° 1.0 or more and less than 20.0, it is desirable to set the heating rate in the intermediate heat treatment process S04 to 1 ℃ / sec or more and 50 ℃ / sec or less, the reached temperature to 200 ℃ or more and 600 ℃ or less, the holding time to 10 sec or more and 500 sec or less, and the cooling rate to 1 ℃ / sec or more and 50 ℃ / sec or less.
[0120] (Finishing rolling process S05)
[0121] Finish rolling is performed to process the copper material after the intermediate heat treatment process S04 into a predetermined shape. In addition, the temperature conditions in this finish rolling process S05 are preferably within the range of -200°C to 200°C, which is cold or hot working, in order to suppress recrystallization during rolling or to suppress a decrease in the ratio of small angle grain boundaries and subgrain boundary lengths, and room temperature is particularly preferred.
[0122] In addition, the rolling reduction rate is appropriately selected to approximate the final shape, but in the finishing rolling process S05, in order to increase the ratio of small-diameter angle grain boundaries and sub-grain boundary lengths and to improve strength through work hardening, and in order to make the average value of the orientation density in the range of the rolled texture φ2 = 20°, φ1 = 20° to 40°, and Φ = 30° to 60° 1.0 or higher, it is preferable to have a rolling reduction rate of 10% or more. In addition, if further strength improvement is sought, it is more preferable to have a rolling reduction rate of 15% or more, and even more preferable to have a rolling reduction rate of 20% or more. Meanwhile, in order to suppress the deterioration of bendability caused by an excessive increase in small angle grain boundaries and subgrain boundaries, and to suppress an excessive increase in the ratio of grains with an aspect ratio b / a of 0.3 or less, and additionally to make the average value of the orientation density in the range of rolled textures φ2 = 20°, φ1 = 20° to 50°, and Φ = 40° to 70° less than 20.0, it is preferable to make the rolling reduction ratio 80% or less, and more preferable to make the rolling reduction ratio 70% or less.
[0123] (Mechanical surface treatment process S06)
[0124] After the finishing rolling process S05, mechanical surface treatment is performed. Mechanical surface treatment is a process that applies compressive stress near the surface after the desired shape has been nearly obtained; this compressive stress near the surface suppresses cracks that occur during bending, thereby improving bendability.
[0125] Mechanical surface treatment can utilize various commonly used methods such as shot peening, blasting, lapping, polishing, buffing, grinding, sandpaper polishing, tension leveler treatment, and light rolling with a low reduction rate per pass (repeated three or more times with a reduction rate of 1 to 10 percent per pass).
[0126] (Finishing heat treatment process S07)
[0127] Next, for the copper material obtained by the mechanical surface treatment process S06, a finishing heat treatment may be performed to remove segregation of contained elements at the grain boundaries and residual deformation.
[0128] In this case, if the heat treatment temperature is excessively high, the small angle grain boundary and subgrain boundary length ratio L LB / (L LB + L HB Given that the strength is significantly reduced, it is desirable to set the heat treatment temperature within the range of 100°C to 800°C. Furthermore, in this finishing heat treatment process S07, it is necessary to set the heat treatment conditions to avoid a significant decrease in strength due to recrystallization. For example, it is desirable to maintain the temperature at 200°C for about 0.1 seconds to 100 seconds, and at 150°C for 1 minute to 100 hours. It is desirable to perform this heat treatment in a non-oxidizing atmosphere or a reducing atmosphere. Although there are no particular limitations on the method of heat treatment, short-duration heat treatment using a continuous annealing furnace is desirable for the effect of reducing manufacturing costs.
[0129] In addition, the finishing rolling process S05, mechanical surface treatment process S06, and finishing heat treatment process S07 described above may be repeated.
[0130] In addition, metal plating (Sn plating, Ni plating, or Ag plating, etc.) may be performed after the finishing heat treatment process S07.
[0131] (Slit processing process S08)
[0132] Slitting is performed on the copper material obtained by the finishing heat treatment process S07 to process it into a desired shape. Slitting is performed by shearing with a slit cutter, but the burrs generated on the copper material at this time become a point of stress concentration during subsequent processing such as edge-wise bending, significantly degrading machinability. If the clearance during slitting increases, the burrs tend to increase as well. However, if the clearance during slitting is excessively small, the entire surface of the slit's cutting plane becomes a shear plane, and since no fracture surface is formed, large burrs called plastic burrs are generated. For this reason, the clearance during slit processing needs to take an appropriate value, and the ratio of clearance to plate thickness (clearance / plate thickness) is preferably 0.5% or more and 12% or less, more preferably 1% or more and 10% or less, and most preferably 2% or more and 8% or less.
[0133] In addition, after slitting, burr removal may be performed to remove burrs generated during slitting. Burr removal can be performed using various commonly used methods such as sandpaper, abrasive sheets, rotary bars, abrasive discs, abrasive belts, and blast treatment.
[0134] In addition, slit processing using precision shearing methods may be used to obtain a burr-free cut surface. Specifically, various commonly used methods can be employed, such as the counter-cut method, which separates materials using reverse shearing and reverse shearing, or the roll slit method, which separates materials using reverse shearing and compression by rolls.
[0135] In this way, the slit copper material of the present embodiment is produced.
[0136] Here, when the plate thickness of the slit copper material is 0.1 mm or more, it is suitable for use as a conductor in high-current applications. In addition, by making the plate thickness of the slit copper material 10.0 mm or less, the increase in load on the press machine can be suppressed, thereby ensuring productivity per unit time and reducing manufacturing costs.
[0137] For this reason, it is desirable to have the plate thickness of the slit copper material within the range of 0.1 mm or more and 10.0 mm or less.
[0138] In addition, it is preferable that the lower limit of the plate thickness of the slit copper material be 0.5 mm or more, and more preferable that it be 1.0 mm or more. Meanwhile, it is preferable that the upper limit of the plate thickness of the slit copper material be less than 9.0 mm, and more preferable that it be less than 8.0 mm.
[0139] In the slit copper material of the present embodiment having the above configuration, since the purity of Cu is 99.96 mass% or higher, conductivity can be secured and it is possible to make the conductivity 97.0% IACS or higher.
[0140] In addition, since the average crystal grain size A at the center of the plate thickness is 25 μm or less, it is possible to improve bendability and yield strength. Also, the occurrence of burrs during slitting can be suppressed, and thus the occurrence of cracks originating from burrs during bending can be suppressed.
[0141] In addition, since the ratio B / A of the average crystal grain size A at the center of the plate thickness and the average crystal grain size B at the surface of the plate thickness is within the range of 0.80 or more and 1.20 or less, localized concentration of stress during processing can be suppressed, thereby improving bendability.
[0142] In addition, in the slit copper material of the present embodiment, if Mg is contained in a range of more than 10 massppm and less than 100 massppm, Mg is dissolved in the matrix of copper, thereby making it possible to improve strength and heat resistance without significantly reducing conductivity.
[0143] In addition, in the slit copper material of the present embodiment, if the heat resistance temperature is 150°C or higher, it can be used stably even in a high-temperature environment.
[0144] In addition, in the slit copper material of the present embodiment, if the 0.2% yield strength in the direction parallel to the rolling direction is greater than 150 MPa, the occurrence of burrs during slitting can be further suppressed, and the occurrence of cracks originating from burrs during bending processing can be suppressed.
[0145] In addition, in the slit copper material of the present embodiment, the analysis is performed by excluding measurement points where the CI value is 0.1 or less, and if the ratio of the number of grains in which the aspect ratio b / a, represented by the major axis a and minor axis b of the grains (including twins) at the center of the plate thickness, is 0.3 or less, is 90% or less of the total number of measured grains, the degree of processing is suppressed, and bending workability can be further improved while maintaining the yield strength.
[0146] In addition, in the slit copper material of the present embodiment, the slit copper material is measured by the EBSD method in steps of measurement intervals that are 1 / 10 or less of the average crystal grain size A at the center of the plate thickness. The total area in multiple fields is 10,000 μm so that a total of 1,000 or more crystal grains are included at the center of the plate thickness. 2For the measurement area exceeding the above, the measurement results are analyzed using the data analysis software OIM to obtain the CI value for each measurement point. Measurement points with a CI value of 0.1 or less are excluded. The orientation difference of each grain is analyzed using the data analysis software OIM. The length of the small angle grain boundary and subgrain boundary, which is the boundary between measurement points where the orientation difference between adjacent measurement points is 2° or more and less than 15°, is L. LB Let L be the length of the large angle grain boundary, which is the boundary between measurement points where the bearing difference between adjacent measurement points is 15° or more. HB ...to be done. At this time, L LB / (L LB + L HB In the case where the relationship is > 10%, a region with high dislocation density is secured, making it possible to improve strength (yield strength) through work hardening.
[0147] In addition, in the slit copper material of the present embodiment, if the average value of the orientation density in the range of φ2 = 20°, φ1 = 20° to 50°, and Φ = 40° to 70° at the center of the plate thickness is 1.0 or higher and less than 20.0, it becomes possible to obtain good bending workability while maintaining even higher yield strength.
[0148] In addition, in the slit copper material of the present embodiment, if the thickness is within the range of 0.1 mm or more and 10 mm or less, parts for electronic and electrical equipment such as bus bars and heat dissipation substrates can be formed by performing stamping or bending processes on the slit copper material.
[0149] In addition, the slit copper material of the present embodiment is particularly suitable as a material for electronic and electrical equipment components such as bus bars and heat dissipation substrates when it has a metal plating layer on its surface.
[0150] As the electronic and electrical device components, bus bars, and heat dissipation substrates of the present embodiment are manufactured using a slit copper material having high yield strength and excellent bendability as described above, it is possible to achieve miniaturization and weight reduction.
[0151] Although the slit copper material and electronic / electrical equipment components (bus bar, heat dissipation substrate, etc.) that are embodiments of the present invention have been described above, the present invention is not limited thereto and can be appropriately modified within the scope of not deviating from the technical requirements of the invention.
[0152] For example, in the embodiment described above, an example of a method for manufacturing a slit copper material was explained, but the method for manufacturing a copper alloy is not limited to that described in the embodiment, and it may be manufactured by appropriately selecting an existing manufacturing method.
[0153] [Example]
[0154] Below, the results of a verification experiment conducted to confirm the effects of the present invention are described.
[0155] By the band melting and refining method, a raw material consisting of so-called 3N Cu with a purity of 99.9 mass% or higher, or a raw material consisting of so-called 5N Cu with a purity of 99.999 mass% or higher, was loaded into a high-purity graphite crucible and melted at high frequency in an atmosphere of Ar gas to obtain molten copper.
[0156] In addition, when Mg was added, a master alloy containing 0.1 mass% of Mg was prepared using high-purity copper of 6N (purity 99.9999 mass%) or higher and a pure metal having a purity of 2N (purity 99 mass%) or higher. This master alloy was added to the obtained molten copper to adjust the composition.
[0157] Then, the molten copper obtained as described above was poured into an insulating material (isoul) mold to produce an ingot with the compositional composition shown in Tables 1 and 2. In addition, the size of the ingot was set to a thickness of approximately 30 mm × a width of approximately 500 mm × a length of approximately 150 to 200 mm.
[0158] For the obtained ingot, heating was performed at 900°C for 1 hour in an Ar gas atmosphere, and then surface grinding was performed to remove the oxide film, and the ingot was cut to a predetermined size.
[0159] After that, cutting was performed by adjusting the thickness to achieve the appropriate final thickness. Each cut sample was rough rolled under the conditions listed in Tables 1 and 2. Subsequently, intermediate heat treatment was performed under the conditions listed in Tables 1 and 2.
[0160] Next, finish rolling (finishing process) was performed under the conditions listed in Tables 1 and 2.
[0161] Then, mechanical surface treatment processes were performed on these samples using the methods described in Tables 1 and 2.
[0162] In addition, buff polishing was performed using #800 polishing paper.
[0163] Sanding was performed using #240 sandpaper.
[0164] Grinder polishing was performed using a bearing foil with a grit of #400 at a rotational speed of 4500 per minute.
[0165] After that, a finishing heat treatment was performed under the conditions listed in Tables 1 and 2. Subsequently, slit processing or precision shearing slit processing (counter-cut method and roll slit method) was performed under conditions where the clearance / plate thickness ratio was 2% to 8%, and slit copper materials were produced such that the plate thickness t, plate width W, and plate thickness t ratio W / t were each as listed in Tables 1 and 2.
[0166] The obtained slit copper material was evaluated for the following items.
[0167] (Composition Analysis)
[0168] Measurement samples were taken from the obtained ingot, and the Mg content was measured by inductively coupled plasma emission spectroscopy, and the Cu content was measured using the copper electrogravimetric method (JIS H 1051). In addition, measurements were taken at two points, one in the center of the sample and the other in the width direction, and the side with the higher content was taken as the content of that sample. As a result, it was confirmed that the composition was as shown in Tables 1 and 2.
[0169] (Average crystal size)
[0170] A sample with a width of 20 mm × a length of 20 mm was cut from the obtained slit copper material, and the average crystal grain size was measured using an SEM-EBSD (Electron Backscatter Diffraction Pa-tterns) measuring device.
[0171] Mechanical polishing was performed using water-resistant abrasive paper and diamond abrasives, with the observation plane being the plane perpendicular to the width direction of the roll, i.e., the TD plane (Transverse direction). Subsequently, a sample for measurement was obtained by performing finish polishing using a colloidal silica solution. Afterward, an EBSD measurement device (Quanta FEG 450 manufactured by FEI, OIM Data Collection manufactured by EDAX / TSL (currently AMETEK)) and analysis software (OIM Data Analysis ver. 7.3.1 manufactured by EDAX / TSL (currently AMETEK)) were used to measure electron beams at an acceleration voltage of 15 kV and 10,000 μm. 2In the above measurement area, the observation surface was measured by the EBSD method in steps of 0.25 μm intervals. The measurement results were analyzed using the data analysis software OIM to obtain CI values for each measurement point. After excluding measurement points with CI values of 0.1 or less, the orientation difference of each grain was analyzed using the data analysis software OIM. Boundaries between adjacent measurement points where the orientation difference was 15° or more were designated as large-angle grain boundaries, and boundaries between adjacent measurement points where the orientation difference was less than 15° were designated as small-angle grain boundaries. In this case, twin boundaries were also treated as large-angle grain boundaries. Additionally, the measurement range was adjusted to include at least 100 grains in each sample. A grain boundary map was created using the large-angle grain boundaries from the results of the obtained orientation analysis. Based on the cutting method of JIS H 0501, five line segments of a predetermined length were drawn vertically and horizontally on the grain boundary map, the number of completely cut grains was counted, and the sum of the cutting lengths (lengths of line segments cut from the grain boundary) was divided by the number of grains to obtain an average value. This average value was taken as the average grain size.
[0172] Then, the average crystal grain size A of the center of the plate thickness (the region from the surface in the plate thickness direction to 25% to 75% of the total thickness) and the average crystal grain size B of the surface layer of the plate thickness (the region from the surface in the plate thickness direction to 20% of the total thickness) were calculated.
[0173] (Aspect ratio of grains)
[0174] Using the aforementioned grain boundary map, the aspect ratio of the grains was measured.
[0175] Five line segments were drawn in the thickness direction and five in the rolling direction for all grains. For the line segments drawn in the rolling direction, the average length of the segments cut at the grain boundaries was defined as the major axis a. For the line segments drawn in the thickness direction, the average length of the segments cut at the grain boundaries was defined as the minor axis b. The aspect ratio b / a, which is the ratio of the lengths of the major axis a and the minor axis b of all grains, was calculated.
[0176] And, the ratio of grains with an aspect ratio b / a of 0.3 or less was calculated.
[0177] (Ratio of small angle grain boundary and subgrain boundary length)
[0178] Using the above-mentioned measurement sample, the observation surface (TD surface) was measured by an EBSD measurement device and OIM analysis software at an electron beam acceleration voltage of 15 kV with a measurement interval step of less than 1 / 10 of the average crystal grain size A at the center of the plate thickness, and the small angle grain boundary and subgrain boundary length ratio were calculated.
[0179] The total area in multiple fields of view is 10,000 µm so as to include a total of 1,000 or more crystal grains at the center of the plate thickness. 2 For the measurement area exceeding the above, the measurement results were analyzed using the data analysis software OIM to obtain the CI values for each measurement point. Excluding measurement points with a CI value of 0.1 or less, the orientation difference of each grain was analyzed using the data analysis software OIM. The boundaries between measurement points where the orientation difference between adjacent measurement points is 2° or more and less than 15° were defined as small-angle grain boundaries and sub-grain boundaries, and their length was L LB It was set as follows. The boundary between adjacent measurement points where the bearing difference is 15° or more is defined as the major angle grain boundary, and its length is L. HB ...was done. The ratio of small-diameter angle grain boundaries and sub-grain boundary lengths L across the entire grain boundary. LB / (L LB + LHB ) obtained.
[0180] (Orientation Density)
[0181] Using the above measurement results, orientation density was measured. Specifically, when calculating the ratio of the small angle grain boundary and subgrain boundary length, the results of measuring the observation plane (TD plane) using an EBSD measuring device and OIM analysis software were used.
[0182] The measurement results were analyzed using the data analysis software OIM to obtain the CI values for each measurement point. After excluding measurement points with CI values of 0.1 or less, the set organization was analyzed using the data analysis software OIM, and a determination orientation distribution function was obtained.
[0183] The determination orientation distribution function obtained by analysis was expressed in terms of Euler angles. Then, the average value of the orientation density was calculated in the range of φ2 = 20°, φ1 = 20° to 50°, and Φ = 40° to 70°.
[0184] (Mechanical properties)
[0185] A No. 13B test specimen specified in JIS Z 2241 was taken from the material for characteristic evaluation, and the 0.2% yield strength was measured by the offset method of JIS Z 2241. In addition, the test specimen was taken from a direction parallel to the rolling direction.
[0186] (Challenge Rate)
[0187] A test specimen with a width of 10 mm × a length of 60 mm was taken from the material for characteristic evaluation, and its electrical resistance was determined using the four-terminal method. Additionally, the dimensions of the test specimen were measured using a micrometer, and its volume was calculated. Then, the conductivity was calculated from the measured electrical resistance value and volume. Furthermore, the test specimen was taken such that its length direction was parallel to the rolling direction of the material for characteristic evaluation. The evaluation results are shown in Tables 3 and 4.
[0188] (Heat resistance temperature)
[0189] The heat resistance temperature (the temperature at which hardness decreases to 80% of the initial value) was evaluated by obtaining an isochronous softening curve based on Vickers hardness during a 1-hour heat treatment, in accordance with JCBA T325:2013 of the Japan Copper Industry Association. In addition, the measurement surface for Vickers hardness was the rolled surface. The evaluation results are shown in Tables 3 and 4.
[0190] (Bending workability)
[0191] Edgewise bending was performed under conditions where the ratio of the radius of curvature (R) to the plate width (W) (R / W) was the value shown in Tables 3 and 4, and the bending portion of the outer side was observed.
[0192] No wrinkles were evaluated as “A” (excellent), wrinkles as “B” (good), small cracks as “C” (fair), and the bend was fractured and edgewise bending could not be performed as “D” (poor). In addition, evaluation results from A to C were judged to be acceptable bendability.
[0193]
[0194]
[0195]
[0196]
[0197] In Comparative Example 1, the Cu content was low at 99.76 mass%, and the conductivity was low at 82.3% IACS.
[0198] In Comparative Example 2, the average crystal grain size A at the center of the plate thickness was large at 120 μm, and the yield strength in the direction parallel to the rolling direction was lowered to 142 MPa. In addition, the bendability became "D".
[0199] Comparative Example 3 has a ratio B / A of the average crystal grain size A at the center of the plate thickness and the average crystal grain size B at the surface of the plate thickness of 3.78, and the bendability is "D".
[0200] In contrast, in Examples 1 to 31 of the present invention, it was confirmed that the conductivity, strength, heat resistance, and bendability were excellent.
[0201] From the above, it has been confirmed that according to the example of the present invention, it is possible to provide a slit copper material having high conductivity, strength, and excellent bendability.
[0202] Industrial applicability
[0203] The slit copper material of the present embodiment is preferably applied to components for electronic and electrical equipment, bus bars, and heat dissipation substrates.
Claims
Claim 1 The purity of Cu is 99.96 mass% or higher, the ratio W / t of plate width W to plate thickness t is 10 or higher, the conductivity is 97.0% IACS or higher, the ratio B / A of the average crystal grain size A at the center of the plate thickness to the average crystal grain size B at the surface layer of the plate thickness is within the range of 0.80 or higher to 1.20 or lower, the average crystal grain size A at the center of the plate thickness is 25 μm or less, the center of the plate thickness is the region from the surface in the plate thickness direction to 25% to 75% of the total thickness, the surface layer of the plate thickness is the region from the surface in the plate thickness direction to 20% of the total thickness, and as an evaluation of bendability, when edgewise bending is performed under the condition that the ratio (R / W) of the radius of curvature (R) to the plate width (W) is 2.50, the bent part does not fracture Slit copper material characterized by not being slit. Claim 2 A slit copper material according to claim 1, characterized by containing Mg in a range of more than 10 massppm and less than 100 massppm, and having a heat resistance temperature of 150 ℃ or higher. Claim 3 A slit copper material according to claim 1 or 2, characterized in that the 0.2% yield strength in a direction parallel to the rolling direction is greater than 150 MPa. Claim 4 A slit copper material according to claim 1 or 2, characterized in that the analysis excludes measurement points where the CI value is 0.1 or less, and the ratio of the number of grains in which the aspect ratio b / a, represented by the major axis a and minor axis b of the grain (including twins) at the center of the plate thickness, is 0.3 or less is 90% or less of the total number of measured grains. Claim 5 In claim 1 or 2, the slit copper material is measured by the EBSD method in steps of measurement intervals that are 1 / 10 or less of the average crystal grain size A at the center of the plate thickness, and the total area in multiple fields of view is 10,000 μm so that a total of 1,000 or more crystal grains are included at the center of the plate thickness. 2 In the measurement area exceeding the above, the measurement results are analyzed using the data analysis software OIM to obtain the CI value for each measurement point, measurement points with a CI value of 0.1 or less are excluded to analyze the orientation difference of each grain, and the length of the small angle grain boundary and subgrain boundary, which is the boundary between measurement points where the orientation difference between adjacent measurement points is 2° or more and less than 15°, is L. LB , the length of the major angle grain boundary, which is the boundary between measurement points where the orientation difference between adjacent measurement points is 15° or more, is L HB When done as, L LB / (L LB + L HB A slit copper material characterized by having a relationship of ) > 10%. Claim 6 A slit copper material according to claim 1 or 2, characterized in that, when the crystal orientation distribution function obtained from texture analysis by the EBSD method at the center of the plate thickness is expressed in Euler angles, the average value of the orientation density in the range of φ2 = 20°, φ1 = 20° to 50°, and Φ = 40° to 70° is 1.0 or more and less than 20.
0. Claim 7 A slit copper material according to claim 1 or 2, characterized in that the thickness is within the range of 0.1 mm or more and 10 mm or less. Claim 8 A slit copper material characterized by having a metal plating layer on its surface in accordance with claim 1 or 2. Claim 9 An electronic or electrical device component characterized by being made using the slit copper material described in claim 1 or 2. Claim 10 A bus bar characterized by being made of a slit copper material as described in claim 1 or 2. Claim 11 A heat dissipation substrate characterized by being made using a slit copper material as described in claim 1 or 2.
Citation Information
Patent Citations
Copper alloy for electronic and electrical equipment, copper alloy plate strip for electronic and electrical equipment, component for electronic and electrical equipment, terminal, busbar, and movable piece for relays
WO2017170699A1
Copper alloy sheet for heat dissipation component, heat dissipation component, and method for producing heat dissipation component
WO2018062255A1
Pure copper plate
WO2020122112A1
Copper plate material for copper plate-attached insulating substrate and method for manufacturing the same
KR1020190134455A